P81 What is the ideal target preterm population that might benefit from the expensive palivizumab prophylaxis?. (15th November 2017) - Tsilika, L; Batra, D; Prayle, AP; Hurley, M; Bhatt, JM
Abstract : Introduction: Palivizumab is a monoclonal antibody that reduces the likelihood of serious respiratory tract infection by Respiratory Syncytial Virus (RSV) in infants with Chronic Lung Disease (CLD) defined as an ongoing oxygen requirement at 36 weeks corrected gestation. In the UK (UK), Palivizumab is offered to high-risk infants with moderate to severe CLD according to their chronological age at the time of RSV season as per Joint Committee on Vaccination and Immunisation (JCVI) guidelines. The American Academy of Paediatrics, in contrast, recommends Palivizumab prophylaxis for all infants born before 29 weeks' gestation who are younger than 12 months at the start of the RSV season. Materials and Methods: We hypothesised that the RSV hospitalisation rate and length of hospital stay (LOS) within the 1 st year of life between preterm babies with CLD immunised according to the JCVI criteria (CLDJCVI) and the additional babies who are considered eligible by the AAP criteria would be comparable. Our cohort included babies born in Nottingham UK between 2009 and 2015. Data was collected from hospital records and the Nottingham CLD database, and analysed using Fisher's exact test for proportions and Mann-Whitney test for continuous data. Results: In total there were 3478 babies born preterm (<37 weeks GA) in Nottingham UK from 2009 to 2015. 459 babies were born in Nottingham at <29 weeks GA. 245 babies had CLD at 36 weeks corrected GA and 135 of these babies were eligible for Palivizumab (JCVI). Conclusion: The RSV hospitalisation rate and LOS were not statistically different in babies under JCVI criteria and additional babies qualifying by AAP criteria. A larger multi-centre prospective study is required to prove health and economic benefits of adopting AAP Palivizumab recommendations.